Long term domiciliary oxygen treatment for chronic respiratory failure reviewed. Issue 3 (March 1990) - Baudouin, S V; Waterhouse, J C; Tahtamouni, T; Smith, J A; Baxter, J; Howard, P
Abstract : The use of long term domiciliary oxygen therapy in the Sheffield area from June to August 1987 has been surveyed. Of the 74 patients prescribed long term domiciliary oxygen therapy, 64 were visited at home. These had arterial blood gas tensions or oxygen saturation measured (while breathing oxygen and air), and the indications for long term domiciliary oxygen therapy were examined retrospectively. Fifty two patients had chronic bronchitis and emphysema, the remainder having pneumoconiosis, bronchiectasis, fibrosing alveolitis, and congestive cardiac failure. Of the 54 cases where indications for treatment could be compared with the Department of Health and Social Security (DHSS) guidelines, only 23 (43%) met the full DHSS criteria before the start of treatment. The median length of treatment was 16 months. At follow up 51 patients had an arterial oxygen tension (PaO2) greater than 8.0 kPa when breathing oxygen. They had a significantly higher PaO2 when breathing air than before long term oxygen therapy (6.7 (SD 1.2) kPa before oxygen treatment, 7.6 (1.4) kPa on reassessment). A similar change was seen in the 23 patients assessed as recommended by the DHSS (6.1 (0.8) kPa; 7.2 (1.2]. PaO2 during the breathing of air was less than 7.3 kPa at reassessment in only 21 (33%) patients. Thirteen patients had carboxyhaemoglobin concentrations above 2.5%, the 95th centile of the distribution in nonsmokers in the laboratory.